Jessie Benton Frémont : Missouri's Trailblazer - Stone, Ilene, 1945- (Book collections on Project MUSE., 2005)
"Chronicles the life of Missouri native Jessie Benton Fremont--firm opponent of slavery and writer of such works as A Year of American Travel and Souvenirs of My Time, daughter of Senator Thomas Hart Benton, and wife of army explorer and first Republican Party nominee John Charles Fremont"--Provided by publisher.